Water pathways: An open source stochastic simulation system for integrated water supply portfolio management and infrastructure investment planning. (October 2020) - Trindade, B.C.; Gold, D.F.; Reed, P.M.; Zeff, H.B.; Characklis, G.W.
Abstract: Financial risk, access to capital, regulatory processes, and regional competition for limited water sources represent dominant concerns in the United States as well as the broader global water supply sector. This work introduces the WaterPaths simulation software: a generalizable, cloud-compatible, open-source exploratory modeling system designed to inform long-term regional investments in water infrastructure while simultaneously aiding regions to improve their short-term weekly management decisions, often made in response to droughts. Uniquely, WaterPaths has the capability to identify coordinated planning and management for groups of water utilities sharing water resources. WaterPaths' exploits dynamic and adaptive risk-of-failure (ROF) rules to trigger management and planning actions in temporally consistent pathways. The compact and efficient ROF-based representation of decision pathways allows WaterPaths to scale efficiently with the number of regional actors and their candidate actions. Lastly, as a platform for supporting decision making under deep uncertainty, WaterPaths accounts for a broad range of uncertainties including hydrological or climate extremes, permitting time, demand growth, effectiveness of water-use restrictions, construction costs, and financing uncertainties. To demonstrate the capabilities of WaterPaths, we introduce a new hypothetical water resources test case, the Sedento Valley. The Sedento Valley test case contains three resource-sharing water utilities that seek to regionally coordinate their policies for drought mitigation and infrastructure investment. The three utilities are challenged by a diverse set of deep uncertainties that encompass natural and human systems stressors. The Sedento Valley test case contributes a new opportunity for benchmarking decision-support tools and water-resources systems simulation software. Highlights: WaterPaths contributes a stochastic simulation to support infrastructure investment pathways. Facilitating coordinated multi-utility regional planning and management. State-aware dynamic and adaptive policy pathways for investment and management actions. The simulation permits the flexible incorporation of broad categories of deep uncertainties. The Sedento Valley hypothetical test case facilitates benchmarking decision support frameworks.